Surviving critical illness: what is next? An expert consensus statement on physical rehabilitation after hospital discharge. Issue 1 (December 2016) - Major, M.; Kwakman, R.; Kho, M.; Connolly, B.; McWilliams, D.; Denehy, L.; Hanekom, S.; Patman, S.; Gosselink, R.; Jones, C.; Nollet, F.; Needham, D.; et al.
Abstract Background The study objective was to obtain consensus on physical therapy (PT) in the rehabilitation of critical illness survivors after hospital discharge. Research questions were: what are PT goals, what are recommended measurement tools, and what constitutes an optimal PT intervention for survivors of critical illness? Methods A Delphi consensus study was conducted. Panelists were included based on relevant fields of expertise, years of clinical experience, and publication record. A literature review determined five themes, forming the basis for Delphi round one, which was aimed at generating ideas. Statements were drafted and ranked on a 5-point Likert scale in two additional rounds with the objective to reach consensus. Results were expressed as median and semi-interquartile range, with the consensus threshold set at ≤0.5. Results Ten internationally established researchers and clinicians participated in this Delphi panel, with a response rate of 80 %, 100 %, and 100 % across three rounds. Consensus was reached on 88.5 % of the statements, resulting in a framework for PT after hospital discharge. Essential handover information should include information on 15 parameters. A core set of outcomes should test exercise capacity, skeletal muscle strength, function in activities of daily living, mobility, quality of life, and pain. PT interventions should include functional exercises, circuit and endurance training, strengthening exercises for limb and respiratory muscles, education on recovery, and a nutritional component. Screening tools to identify impairments in other health domains and referral to specialists are proposed. Conclusions A consensus-based framework for optimal PT after hospital discharge is proposed. Future research should focus on feasibility testing of this framework, developing risk stratification tools and validating core outcome measures for ICU survivors.